2016
DOI: 10.2147/jbm.s84848
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to encourage physical activity in patients with hemophilia to improve quality of life

Abstract: Hemophilia is a bleeding disorder caused by a congenital abnormality of blood coagulation. Until the mid-1970s, patients with hemophilia (PWH) were advised to refrain from physical activity (PA) because of a perceived increased risk of bleeding. Since then, PA, which is recognized as being essential for health maintenance, is now recommended by the World Federation of Hemophilia. Moreover, a number of studies reported that PA can improve treatment efficacy and prevent bleeding in PWH. Physical assessment and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 59 publications
1
37
0
5
Order By: Relevance
“…In the context of haemophilia, however, a careful consideration of the individual's risk of bleeding (both real and perceived) and level of pain and functional impairment is critical in designing a safe and effective exercise regimen. For example, important steps to facilitate regular activity may include selecting low‐impact aerobic activities such as swimming, walking or cardiovascular training using an elliptical machine or stationary bike, reducing the intensity of resistance exercises, incorporating a stretching routine and recognizing and managing the risk of activity‐related pain or bleeding . Advising PWH on which types and intensities of activities to engage in, how to adjust their treatment regimens to accommodate exercise and how to manage potential activity‐related bleeding are therefore important responsibilities of the haemophilia care team.…”
Section: Application Of General Guidelines For Weight Managementmentioning
confidence: 99%
“…In the context of haemophilia, however, a careful consideration of the individual's risk of bleeding (both real and perceived) and level of pain and functional impairment is critical in designing a safe and effective exercise regimen. For example, important steps to facilitate regular activity may include selecting low‐impact aerobic activities such as swimming, walking or cardiovascular training using an elliptical machine or stationary bike, reducing the intensity of resistance exercises, incorporating a stretching routine and recognizing and managing the risk of activity‐related pain or bleeding . Advising PWH on which types and intensities of activities to engage in, how to adjust their treatment regimens to accommodate exercise and how to manage potential activity‐related bleeding are therefore important responsibilities of the haemophilia care team.…”
Section: Application Of General Guidelines For Weight Managementmentioning
confidence: 99%
“…There are conflicting data in the literature about the amount of exercise regularly performed by people with hemophilia,9, 11, 12 and boys and teens with hemophilia report barriers to exercise and are unsure of options 12…”
Section: Introductionmentioning
confidence: 99%
“…Multiple barriers to exercise have been isolated including: pain,13, 14, 15 concerns about joint damage,8, 13, 16, 17 limited time and self‐motivation,8, 18 and lack of knowledge among health‐care providers 16, 17. Commonly identified facilitators to activity in these populations include: relief of pain,8 maintaining independence,8, 13 a trusting relationship with health‐care providers,8, 9 and social and emotional benefits 8, 13, 18, 19, 20, 21, 22. To our knowledge, previous research regarding exercise beliefs in people with hemophilia has all been qualitative in nature,10, 12, 23 suggested that people with hemophilia report barriers that are similar to those found in arthritis10, 12, 24 and that men with severe hemophilia want to exercise despite any limitations due to their disease 10.…”
Section: Introductionmentioning
confidence: 99%
“…Together these data provide broad‐based insights into risks associated with many physical activities that PTs who treat people with haemophilia may encounter. Whereas other studies have focused on general strategies to reduce bleeding risk among people with haemophilia (eg, incorporating a stretching routine or ensuring appropriate prophylactic coagulation factor treatment), our data focus on how specific risks differ between activities, and which risk drivers can be modified to facilitate participation in specific activities. Based on the multi‐specialist focus group that was held to explore these data, the authors developed discussion guides that parents (Appendix ) and adult patients (Supplemental Appendix ‐ online only) may use to prepare them for conversations with their HTC about planned participation in activities.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with haemophilia are now recommended to engage in physical activity to improve physical fitness and promote normal neuromuscular and bone development . General benefits of physical activity include improvements in strength, flexibility and self‐image, and decreased risk for several diseases, such as diabetes, obesity and cardiovascular disease . Additionally, for people with haemophilia, regular participation in activity may prevent or reverse disease‐related losses in bone density or body coordination, and may decrease the risk for spontaneous joint bleeding …”
Section: Introductionmentioning
confidence: 99%